췌두부십이지장 영역의 혈관해부학 연구 - 이태희(Tae Hee Lee); 박동은(Dong-Eun Park); 소병준(Byung-Jun So); 채권묵(Kwon-Mook Chae) (Annals of surgical treatment and research, 2002)
Purpose: Duodenum-preserving pancreatic head resection (DPPHR) is a suitable surgical procedure in the treatment of benign pancreatic head tumor, chronic pancreatitis and low-grade malignancy of pancreatic head. The main advantage of this procedure is the preservation of the duodenum, which plays a key role in digestive functions. To create a practical guideline for vascular preservation during DPPHR, we examined the anatomy of pancreaticoduodenal arteries (PDA) by specimen angiography. Methods: From March 2000 to September 2001, 9 specimens were obtained from patients undergoing pancreaticoduodenectomy. As soon as the specimens were obtained, 4 PDA were cannulated and specimen angiography was performed. Results: Arcade formation between the superior and inferior PDA was found in all of the cases. The anterior inferior PDA and posterior inferior PDA exhibited common trunk formation. Many communicating arteries between both arcades were found. The papillary branch, originating from the posterior superior PDA, was found in 4 cases. Conclusion: To preserve the blood supply to the duodenum, complete preservation of both arteries may not be necessary. However, the preservation of the posterior superior PDA may be needed to maintain the blood supply of the papillary and distal bile ducts. (J Korean Surg Soc 2002; 63:155-159) KCI Citation Count: 0